Al-Wasatiyyah in the practice of religious tolerance among the families of new Muslims in sustaining a well-being society - Khadijah Mohd Khambali @ Hambali; Suraya Sintang; Azarudin Awang; Khairul Nizam Mat Karim; Nur Farhana Abdul Rahman; Wan Adli Wan Ramli; Nurhanisah Senin; Azmil Zainal Abidin; Ahmad Zuhdi Ismail; Wan Zailan Kamaruddin Wan Ali; Ruzman Md. Noor (Emerald Group Publishing Ltd., 2017)
Purpose – The main value in a culture of tolerance is wasatiyyah. The fragility of relationships and misunderstanding between Muslim and non-Muslim communities occurs when attention to values of tolerance which need more attention on moderation was not practiced especially in the life of a new Muslim convert community. Thus, the practice of moderation is one mechanism proposed by the government to ensure a harmonious continuation of life in a religious community can be achieved. For that, a qualitative study design was used to describe the current status of a phenomenon that occurs among new Muslim converts. The purposive sampling method is used to determine the applications of wasatiyyah in new Muslims’ life tolerance at Kota Kinabalu (East Malaysia) and Kuala Terengganu (West Malaysia). Although the study was conducted at two different locations, there is a relationship between religious phenomena that occur in the new Muslims community in Malaysia. The purpose of this study is to see the practical concept of moderation in the life of new Muslims and their relation with Muslims and non-Muslims. The results showed that the value of moderation was applied in the aspect of tolerance. The application of Wasatiyyah in practice of tolerance had helped non-Muslims family members to change their attitudes and perception towards Islam. This study suggests the values of wasatiyyah in the life of religious tolerance, need to be nourished especially in multiethnic society when sharing a living places, education and employment for better social development as well as a well-being pluralistic society. Design/methodology/approach – The study was conducted through descriptive data qualitative methods. Purposive sampling was used which refers to a group that has the characteristics of samples required by researchers (Mohd Najib Abdul Ghafar 2003). This study applies the method of in-depth interview with the selected new Muslims around Kota Kinabalu (representing East Malaysia) and around Kuala Terengganu (representing Peninsular Malaysia / West Malaysia).Thus, data accumulation involves new Muslims(new Converts) from various ethnics (Sabahan and Sarawakian) which comprise Kadazandusun, Murut, Rungus, Sino and Iban. Secondly, those are from the Peninsular Malaysia which includes Chinese and Indian. Whereas in Kuala Terengganu, data accumulation involves new Muslims from various ethnics (Chinese, Indian, Sarawakian and others). The result of the interview is shown through descriptive narratives which display the practice of tolerance in the form of supportive interaction from the non-Muslim families towards the new Muslims in Islamic lifestyle. Findings – The concept of wasatiyyah has nurturing tolerance among Muslim, newly Muslim and non-Muslim as well as fostering harmony among the diverse ethnics in Malaysia. Based on the discussion, it was observed that the concept of wasatiyyah had a great influence on the relationship among Muslim, newly Muslim and non-Muslim, as it had a strong link with the value of akhlaq that have been embedded in the Muslim community. The wasatiyyah is the main element that shapes the relationship, and it is the results of interaction with social norms, for it has bred certain social values that include tolerance, compromise, modesty, respect and cooperation as transpired when they (Muslim and newly Muslim) interact among themselves or with other communities. Furthermore, the main goal for the concept is to maintain peace and built well-being in the society as well as bracing racial ties in Malaysia, especially among Muslim, newly Muslim and non-Muslim. Originality/value – Tolerance is a culture that founded the co-existence of pluralistic society in Malaysia. The culture of tolerance can only be built if ethnic tolerance and religious tolerance is accepted as a common practice – Muslims and non-Muslims alike. The description of wasatiyyah in the practice of religious tolerance among the families of new Muslims is the platform towards the acculturation of tolerance in the societal life from different faith and ethnics. It can be said that the higher the tolerance of ethnic, the higher is the religious tolerance, which is manifested through the application of wasatiyyah between people from different religions. This situation is highlighted in the relations of Muslim, newly Muslim and non-Muslim in Sabah and Terengganu where the culture of tolerance is apparent in the life together. Extensive interaction through encounters, acquaintance and co-existence that shape the friendship, brotherhood and kinship is the best formula in nurturing the culture of tolerance in the pluralistic society of Malaysia. Perhaps, the concept of wasatiyyah may be implemented in the whole aspect of life in the context of Malaysia. It is because the term wasatiyyah has the main sources of Islamic epistemology as well as sustaining the well-being pluralistic society without destroying the differences.